Sistem Pendukung Keputusan terhadap Jenis dan Penerima dalam Penentuan Bantuan Desa Menggunakan Metode Simple Additive Weighting - Nandes, Randi Afri (Jurnal Informatika Ekonomi Bisnis, 2021)
Sidoluhur Village is a village located in Padang Jaya District, North Bengkulu which has a large population. The his village has 3 hamlets in one village. The problem in Sidoluhur Village is that it is difficult to determine the recipient of village assistance, because the number of aid proposals that are proposing is more than the number of people who receive assistance. There are so many proposals that have been submitted, this is of course very troublesome for village officials who choose to receive assistance. As problems develop, a decision support system is needed that will provide results on the computer to determine who should get help. A decision support system is a system for finding decision support, decisions are taken using a system designed based on usage needs, in helping to make decisions, decisions are designed based on predetermined criteria and alternatives and have a system that is structured and programmed in the form of weighting that will be accumulated and normalized and produce ranking. This study uses the Simple Additive weighting method, commonly referred to as a method that uses a weighted additive form. The form of the method is to calculate the total weight value of the work steps on the existing alternatives of all attributes. To explain about the completion of the method uses village aid recipient data. A lot of data that will be used as alternatives in this study are 9 candidates for village aid recipients. As a result, the recipients of aid should not be less than 0.5000, with the result that 7 recipients of assistance and 2 people who are not eligible to receive assistance.